2013
DOI: 10.1093/molbev/mst063
|View full text |Cite
|
Sign up to set email alerts
|

Testing for Associations between Loci and Environmental Gradients Using Latent Factor Mixed Models

Abstract: Adaptation to local environments often occurs through natural selection acting on a large number of loci, each having a weak phenotypic effect. One way to detect these loci is to identify genetic polymorphisms that exhibit high correlation with environmental variables used as proxies for ecological pressures. Here, we propose new algorithms based on population genetics, ecological modeling, and statistical learning techniques to screen genomes for signatures of local adaptation. Implemented in the computer pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
879
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 667 publications
(888 citation statements)
references
References 58 publications
2
879
1
6
Order By: Relevance
“…Signatures of local adaptation to climate were investigated using two GEA methods that take into account neutral population structure: Bayenv2 (Coop et al., 2010; Gunther & Coop, 2013) and LFMM (Frichot et al., 2013). We first ran Bayenv2 using the entire SNP dataset and 100,000 Markov Chain Monte Carlo (MCMC) runs to estimate the covariance matrix (Figure S2, Appendix S2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Signatures of local adaptation to climate were investigated using two GEA methods that take into account neutral population structure: Bayenv2 (Coop et al., 2010; Gunther & Coop, 2013) and LFMM (Frichot et al., 2013). We first ran Bayenv2 using the entire SNP dataset and 100,000 Markov Chain Monte Carlo (MCMC) runs to estimate the covariance matrix (Figure S2, Appendix S2).…”
Section: Methodsmentioning
confidence: 99%
“…Loci showing signatures of selection are often detected by testing for atypically high or low among‐population genetic differentiation compared with the rest of the genome ( F ST outlier tests; Lewontin & Krakauer, 1973; Beaumont & Nichols, 1996; Beaumont & Balding, 2004; Foll & Gaggiotti, 2008; Excoffier, Hofer, & Foll, 2009), or by looking at correlations with environmental factors of interest after controlling for neutral population structure (genetic‐environment associations, GEA; Coop, Witonsky, Di Rienzo, & Pritchard, 2010; Frichot, Schoville, Bouchard, & François, 2013; Gunther & Coop, 2013). These methods show variable performances under different demographic scenarios (Excoffier et al., 2009; Frichot, Schoville, de Villemereuil, Gaggiotti, & François, 2015; Lotterhos & Whitlock, 2014, 2015; de Villemereuil, Frichot, Bazin, François, & Gaggiotti, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used genotype by sequencing (GBS; Peterson et al., 2012) of two Illumina Hiseq libraries, de novo assembly into 90‐bp GBS tags with STACKS (Catchen, Amores, Hohenlohe, Cresko, & Postlethwait, 2011), latent factor mixed modeling [a genotype–environment association (GEA) method; Frichot, Schoville, Bouchard, & François, 2013], and two F ST outlier methods (Excoffier, Hofer, & Foll, 2009; Foll & Gaggiotti, 2008) to classify putatively neutral SNPS and SNPs exhibiting varying support for being under selection (Pais et al., 2016). Putatively neutral reference SNPs were used to calculate marker‐based inbreeding coefficients ( F ; Keller, Visscher, & Goddard, 2011) and identity‐by‐state matrices using PLINK (Purcell et al., 2007).…”
Section: Methodsmentioning
confidence: 99%
“…The reasons for the popularity of GEA analyses are practical: They require no phenotypic data or prior genomic resources, do not require experimental approaches (such as reciprocal transplants) to demonstrate local adaptation, and are often more powerful than differentiation‐based outlier detection methods (De Mita et al., 2013; de Villemereuil, Frichot, Bazin, François, & Gaggiotti, 2014; Forester, Lasky, Wagner, & Urban, 2018; Lotterhos & Whitlock, 2015). In particular, participants considered how and why detection rates differed between univariate and multivariate GEAs, exploring the use of latent factor mixed models (Frichot, Schoville, Bouchard, & Francois, 2013) and redundancy analysis (Forester, Jones, Joost, Landguth, & Lasky, 2016; Lasky et al., 2012), respectively. Recent work has shown that RDA is an effective means of detecting adaptive processes that result in weak, multilocus molecular signatures (Forester et al., 2018), providing a powerful tool for investigating the genetic basis of local adaptation and informing management actions to conserve evolutionary potential (Flanagan et al., 2017; Harrisson et al., 2014; Hoffmann et al., 2015).…”
Section: Improving Downstream Computational Analysesmentioning
confidence: 99%